Comparative Analysis of Risk-Based and Time-Based Inspection Application in Hydrocarbon and Chemical Industries: A Review - Azizar, Azizar; Sofyan, Nofrijon (Journal of Materials Exploration and Findings, 2024)
RBI and TBI strategies are comparatively reviewed in terms of their contribution to maintaining asset integrity for asset owners in the hydrocarbon and chemical industries. The objective is to assess various methods on a cost-efficient and risk-managed operational safety basis. It utilizes common industry standards such as API 580 for RBI, and API 510, API 570, and API 653 for TBI, and also case studies and literature analysis. The analysis of data was conducted to examine how each approach deals with inspection planning and decision-making. They suggest that RBI's risk-based prioritization strategy leads to more effective management of high-risk assets, while TBI is simpler and standardized, but could potentially result in over-inspections or overlook emerging risks. The review thus suggests a customized strategy taking account of both RBI and TBI in order to adequately meet requirements related to operational processes, risk exposure, and compliance.